2021
DOI: 10.1038/s41418-020-00729-0
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure—emerging roles for the mitochondrial pyruvate carrier

Abstract: The mitochondrial pyruvate carrier (MPC) is the entry point for the glycolytic end-product pyruvate to the mitochondria. MPC activity, which is controlled by its abundance and post-translational regulation, determines whether pyruvate is oxidised in the mitochondria or metabolised in the cytosol. MPC serves as a crucial metabolic branch point that determines the fate of pyruvate in the cell, enabling metabolic adaptations during health, such as exercise, or as a result of disease. Decreased MPC expression in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Instead, it is Frontiers in Pharmacology frontiersin.org metabolized in the cytosol, primarily reduced to lactate, as well as to other metabolites such as involving in propanoate metabolism (Cluntun et al, 2021). In previous reports on hypertrophic cardiomyopathy patients and mice (Fernandez-Caggiano et al, 2020;Fernandez-Caggiano and Eaton, 2021), decreased MPC expression is sufficient to cause metabolic cardiac remodeling, hypertrophic growth and ultimately heart failure, the abundance determines the extent of pyruvate being metabolically oxidized in the mitochondria. Moreover, it is reported that the monocarboxylate transporter 4 (MCT4) inhibition can prevent and reverse cardiomyocyte hypertrophy, which is consistent with decreased pyruvate flux in mitochondrial (Cluntun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is Frontiers in Pharmacology frontiersin.org metabolized in the cytosol, primarily reduced to lactate, as well as to other metabolites such as involving in propanoate metabolism (Cluntun et al, 2021). In previous reports on hypertrophic cardiomyopathy patients and mice (Fernandez-Caggiano et al, 2020;Fernandez-Caggiano and Eaton, 2021), decreased MPC expression is sufficient to cause metabolic cardiac remodeling, hypertrophic growth and ultimately heart failure, the abundance determines the extent of pyruvate being metabolically oxidized in the mitochondria. Moreover, it is reported that the monocarboxylate transporter 4 (MCT4) inhibition can prevent and reverse cardiomyocyte hypertrophy, which is consistent with decreased pyruvate flux in mitochondrial (Cluntun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown abnormal energy metabolism in MI disease states [16]. Pyruvate was not only the product of the glycolysis pathway, but also of the carboxylation of pyruvate, which was an essential physiological process to maintain normal heart function [17]. The tricarboxylic acid cycle played a central role in oxidative phosphorylation of the myocardium, so under normal conditions, the contents of tricarboxylic acid intermediates such as malic acid and succinic acid were strictly regulated by the body [18].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria also produce ROS and energy [ 44 ]. Excessive accumulation of ROS can lead to the abnormal opening of the mitochondrial permeability transition pore, thereby regulating the permeability of the mitochondrial membrane and causing an imbalance in ion concentrations inside and outside the mitochondria [ 55 ]. ROS can activate various transcription factors, such as the Cyt-C transferase, BAX, and caspase pathways.…”
Section: Regulation Of Cardiotoxic Injury and Mitochondrial Homeostas...mentioning
confidence: 99%